An Appraisal of the Legal Bottom-Line of Corporate Environmental Responsibility in Ethiopia - Bishaw, Ayalew Abate (Bahir Dar University Journal of Law, 2023)
While working towards attracting huge investment and promoting business whether or not developing countries have the necessary environmental legal regime to hold corporations legally liable is often an issue. In an effort to partly respond on the issue, this article is meant to assess the minimum environmental law requirements applied for holding business entities (both foreign and domestic) liable to their environmental misdemeanors in Ethiopia-‘the legal bottom lines of corporate environmental responsibility.’ The legal bottom lines of corporate environmental responsibility are requirements that corporations or business organizations are legally mandated to comply with. The purpose of this article is therefore to ascertain whether Ethiopia has the necessary environmental and related legal foundational frameworks to holding corporations accountable- determining the minimum legal framework. For this purpose doctrinal analyses were preferred as a method and assessment was made on relevant laws. Accordingly, the assessment finds that Ethiopia has foundational environmental legal regime and if applied may hold corporations liable. It further unearths that still the laws lack clarity; comprehensiveness and adequacy to flatteringly control businesses conduct to the contemporary requirements. Hence for a proper corporate environmental regulation, further amendment need to be made.